THE DEVELOPMENT OF GOOD PRACTICES FOR ENGLISH LANGUAGE TEACHER REDEPLOYMENT POLICY IMPLEMENTATION IN MALAYSIA - Nor Hisham Ismail; Yusof, Hamidah; Khalip Musa (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The quality of English teachers in schools is one of the contributing factors in students’ proficiency in the language. Hence, the purpose of this study was to explore and develop teacher redeployment good practices. The needs analysis of this study discovered the themes of redeployment good practices. This study used the triangulation method in collecting information from interviews, observation, and document analysis. Fuzzy Delphi Method (FDM) was adopted to develop good practices of teacher redeployment policy implementation based on the consensus of experts. There were six themes constructed and 42 sub items supported the themes to develop the redeployment policy implementation best practices priority list. 15 panel of experts responded to Five-Likert linguistic scale survey questionnaires. The threshold value (d) must exceed 75% to verify the experts’ consensus, while the alpha-cut value > 0.5 was used to select the items. This study showed a high consensus agreement among the experts for themes with (d) values at 85.7% in terms of the Teacher Selection Based on Professional Background (Amax = 0.79), Interventions (Amax = 0.78), Teacher Readiness (Amax = 0.77), Implementation of The Guidelines (Amax = 0.77), Teacher Selection Based on Personal Background (Amax = 0.77), the Enforcement of Policy Implementation (Amax = 0.74) and all values exceeded the minimum of 0.60. Therefore, based on the findings, the implication of the study recommends the policymakers to review the current redeployment guidelines so that it can support the efforts to minimize mismatch of English teachers in terms of the location and option thus will improve the management of the policy implementation.